Taxonomy of spatially disjunct alpine Teleiopsis albifemorella s. lat. (Lepidoptera: Gelechiidae) revealed by molecular data and morphology —how many species are there? - Huemer, Peter; Mutanen, Marko (Zootaxa, 2012)
The taxonomy of the European alpine species Teleiopsis albifemorella (Hofmann, 1867) s. lat. is revised. We sequenced mtDNA markers (COI barcode region) of 44 specimens resulting in a full barcode for 41 specimens. We also sequenced five nuclear markers (CAD, EF-1a, IDH, MDH and wingless) of 12 specimens. Molecular data of nuclear genes combined with weak morphological characters indicate two species: Teleiopsis albifemorella from the eastern Alps and the Dinaric mountains and Teleiopsis paulheberti sp. nov. from the southwestern Alps, the Apennines and the Pyrenees. The COI barcode region groups into seven genetic lineages from geographically coherent areas. Four major haplogroups are assigned to T. paulheberti sp. nov. whereas three major haplogroups support the eastern alpine Teleiopsis albifemorella.